NEWS2 score in the practice of infectious diseases hospital in COVID-19 patients. Implementation and results - К. N. Popova; A. A. Zhukov; I. L. Zykina; D. V. Troschanskiy; I. N. Tyurin; D. N. Protsenko (Вестник анестезиологии и реаниматологии, 2021)
Amidst the new COVID-19 pandemic, there is a need for a reliable medical tool to monitor patients’ vital conditions with clinical information continuity. This tool is essential for timely detection of the risk of the patient’s clinical state deterioration throughout all the stages of medical assistance.  The objective is to assess results of the NEWS2 score implementation at the in-patient stage of medical care.Methods. 183,732 scores of the NEWS2 score in 10,290 hospitalized patients were analyzed.  All the assessed results of the NEWS2 score were retrospectively analyzed. The NEWS2 score results were added to the United Medical Information and Analytical System of Moscow (EMIAS) database through the NEWS2 mobile application. The researchers analyzed the descriptive statistics of the score; the prognostic significance of NEWS2 in the prediction of the disease outcome was assessed as well as the accuracy of the used methods. Results. As the result of the research, deviations from standard methods in the application of the NEWS2 score were outlined, which allowed the researchers to develop the corrective measures.  The received data confirmed that interval assessment by the NEWS2 score and the trend analysis were important when making clinical and organizational decisions. Specific parameters of the score use during the COVID-19 pandemic were outlined, which helped to adjust the in-hospital procedures for clinical decision-making process, routing, and the continuity of all stages of medical assistance was established. Conclusion. The use of the NEWS2 score in medical practice makes it possible to predict the risks of clinical deterioration in the patient's condition, conduct bedside monitoring of therapy effectiveness, and optimize in-hospital routing. However, to ensure the validity of the score, it is necessary to plan activities for the personnel training and motivation, as well as to monitor careful adherence to the protocol.